Shuffle and draw - Dial, Tabitha, author; Beachy-Quick, Dan, 1973-, advisor; Steensen, Sasha, committee member; Lehene, Marius, committee member (Colorado State University. Libraries, 2009)
Using my own worn Universal-Waite Tarot deck, I wrote a large number of poems while an MFA candidate at Colorado State University. "Five of Pentacles". "The Hanged Man" and "The Empress" are ekphrastic and attempt to verbalize Tarot cards of the same names. Storylines within this thesis began with the Arms suit, a suit created after reading Barbara Walker's study of her Tarot, The Secrets o/the Tarot: Origins. History, and Symbolism. Each of her suits developed myths and symbols, using a direction I wanted to take, after straight ekphrasis of most of the 78 cards produced interesting writing, but poems that were not full and provocative. I came to produce my own versions of-other major arcana cards while studying Walker and others. Only one Cups poem emerges in this thesis. Because the Cups represent the emotions, the implication might be that Tarot-interpretations of emotional maturity are stunted in my collection because there is only one Cup cards/poem. But the poem remains true to the original ekphrastic spirit of my work. The creation of my own poems/suits, some that address the poem reader/Tarot reader, fill in for Cups psyche.
Keywords: Tarot cards -- Poetry; Tarot -- Poetry